2015
DOI: 10.1007/s00345-015-1691-4
|View full text |Cite
|
Sign up to set email alerts
|

PREDICT: model for prediction of survival in localized prostate cancer

Abstract: PurposeCurrent models for prediction of prostate cancer-specific survival do not incorporate all present-day interventions. In the present study, a pre-treatment prediction model for patients with localized prostate cancer was developed. MethodsFrom 1989 to 2008, 3383 patients were treated with I-125 brachytherapy (n = 1694), external beam radiotherapy (≥74 Gy, n = 336) or radical prostatectomy (n = 1353). Pre-treatment parameters (clinical T-stage, biopsy grade, PSA and age) were related to the hazard of mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Sixteen additional studies were identified by reviewing the references of excluded but relevant studies. A total of 12 studies were eligible for inclusion in the final review 21–32. Two of these had not been summarised in previous reviews 26 27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen additional studies were identified by reviewing the references of excluded but relevant studies. A total of 12 studies were eligible for inclusion in the final review 21–32. Two of these had not been summarised in previous reviews 26 27.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies were eligible for inclusion in the final review 21–32. Two of these had not been summarised in previous reviews 26 27. The PRISMA flow diagram is shown in figure 1, including the reasons for exclusion at full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…Although these extensions add granularity, they remain too heterogeneous for modern individualised medicine approaches. More recent attempts at developing survival models have focussed solely on men undergoing radical treatment, and have not been appropriately validated [ 11 , 12 ]. The inadequacies of existing models are evident by the fact that the American Joint Committee on Cancer (AJCC) has not endorsed a single prognostic model for nonmetastatic PCa [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ten-year estimates of prostate cancerspecific mortality have consistently been less than 10%, for both men with lowrisk disease treated with dose-escalated radiation therapy (RT) (1-3) and men with higher-risk disease treated with RT in conjunction with androgen deprivation therapy (ADT) (2-5). Since the rate of death due to prostate cancer is relatively low, the overall risk of death tends to be driven by competing risks (6)(7)(8) (24), and the use of ADT (2-5), owing to past research that showed an effect of these factors on survival.…”
mentioning
confidence: 99%